Assessment of global and regional UPD for BDS/GNSS PPP-AR at low latitudes during quiet and geomagnetic storm periods - Jun Tang; Wei Zhang; Yibin Yao; Chaoqian Xu; Liang Zhang; Youkun Wang (International Journal of Applied Earth Observations and Geoinformation, 2024)
The resolution of ambiguity (AR) is of paramount importance for the precise point positioning (PPP) technique, as it enables the reduction of convergence duration and the improvement of positioning accuracy. Uncalibrated phase delay (UPD) is a key factor in ambiguity fixation. We investigate the difference between different scale UPD estimates which are obtained from MGEX and YNCORS stations in PPP-AR performance during quiet and geomagnetic storm periods. The conclusion is supported by two sets of experiments which indicate that regional UPD estimates offer higher stability and accuracy. In the quiet period, the average time to first fix (TTFF) of the regional UPD-based PPP-AR is enhanced by 35.75% compared with the global UPD-based PPP-AR, the N-direction accuracy is enhanced by 60.32%, the E-direction accuracy is decreased by 6.36%, the U-direction accuracy is decreased by 56.14%, and the convergence rate is enhanced by 7.5% to reach 100%. During the period of geomagnetic storm, the average initialization time of regional UPD-based PPP-AR is 32.05% faster than the average initialization time of global UPD-based PPP-AR. the N-direction accuracy is enhanced by 90.32%, the E-direction accuracy is decreased by 61.11%, the U-direction accuracy is enhanced by 55.18%, and the convergence rate is enhanced by 6.67%. Additionally, the TTFF of PPP-AR based on regional UPD is significantly shorter and more stable. The difference may be due to the regional UPD absorbing part of the common error caused by the geomagnetic storm, which results in a greater enhancement in the accuracy and stability of the regional UPD product during the storm.